Using YouTube Video to Improve Students’ Speaking Skill at Eleventh of SMA Wahidiyah Gumukmas Jember - Jenny Ika Misela; Mahendra Puji Permana Aji (Kirana Publisher (KNPub), 2023)
This research was direction to improve students’ speaking skill though YouTube Video and to know how the implementation of the technique improving students’ speaking skill in English speaking. This research was accomplished at Eleventh of SMA Wahidiyah Gumukmas Jember in which consisted of 4 students as respondent. To solve students’ problem in teaching learning English especially in speaking skill, the researcher applied Classroom Action Research (CAR) designed by Burns which consisted of four phases; planning, acting, observing and reflecting, on each cycle. There were two kinds of data gained in this study; qualitative and quantitative data. The qualitative data can derive from the observation, fieldnote and interview. Meanwhile, the quantitative data can derive from the pre-test and post-test. The result of this study showed that the implementation of YouTube Video to improve students’ speaking skill was successful. It was proven by the data that were collected from this study. The qualitative data showed improvement of the students’ motivation, interest and confident to speaking English after the implementation of YouTube Video as media. The result of the test showed improvements in students’ speaking score. In pre-test, there was no one students 0% who pass the minimum mastery criterion KKM out of 4 students which the mean score was only 55. Then, in post-test for cycle I, the percentage of students who passed the minimum mastery criterion KKM improve to 50% or 2 out of 4 students passed the minimum mastery criterion KKM with 70 as the mean score. Next, in post-test for cycle II, the mean score was 82. The result of the test shows significant improvement where 100% of the students could achieve the score above the minimum criterion which at least 75. Based on the result above, YouTube Video may be concluded successfully improve students’ speaking skill.